2000
DOI: 10.1016/s0375-9601(00)00163-8
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on Duffin–Kemmer–Petiau theory and gauge invariance

Abstract: Two problems relative to the electromagnetic coupling of Duffin-Kemmer-Petiau (DKP) theory are discussed: the presence of an anomalous term in the Hamiltonian form of the theory and the apparent difference between the Interaction terms in DKP and Klein-Gordon (KG) Lagrangians. For this, we first discuss the behavior of DKP field and its physical components under gauge transformations.From this analysis, we can show that these problems simply do not exist if one correctly analyses the physical components of DKP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
154
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 8 publications
2
154
0
2
Order By: Relevance
“…Although the formalisms are equivalent in the case of minimally coupled vector interactions [5][6][7], the DKP formalism enjoys a richness of couplings not capable of being expressed in the KG and Proca theories [8,9]. Recently, there has been increasing interest in the so-called DKP oscillator [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the formalisms are equivalent in the case of minimally coupled vector interactions [5][6][7], the DKP formalism enjoys a richness of couplings not capable of being expressed in the KG and Proca theories [8,9]. Recently, there has been increasing interest in the so-called DKP oscillator [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, J 1 for a stationary state, as expressed by (9) and (14), is the same at all points of the X-axis and vanishes for a bound-state solution (because Φ σ vanishes as x → ∞), so we demand that s σ ∈ R and so α σ ≥ α crit . Normalizability of Φ σ also requires s σ > −1/2 and due to the two-fold possibility of values of s σ for α crit < α σ < 3/(8m), it seems that the solution of our problem can not be uniquely determined.…”
Section: The Linear Plus Inversely Linear Potentialmentioning
confidence: 99%
“…The onus of equivalence between the formalisms represented an objection to the DKP theory for a long time and only recently it was shown that they yield the same results in the case of minimally coupled vector interactions, on the condition that one correctly interprets the components of the DKP spinor [5]- [6]. However, the equivalence between the DKP and the Proca formalisms has already a precedent [7].…”
Section: Introductionmentioning
confidence: 99%